Contextual Modulation of Vocal Behavior in Mouse: Newly Identified 12 kHz “Mid-Frequency” Vocalization Emitted during Restraint - Grimsley, Jasmine M. S.; Sheth, Saloni; Vallabh, Neil; Grimsley, Calum A.; Bhattal, Jyoti; Latsko, Maeson; Jasnow, Aaron; Wenstrup, Jeffrey J. (Frontiers in Behavioral Neuroscience, 2016)
While several studies have investigated mouse ultrasonic vocalizations (USVs) emitted by isolated pups or by males in mating contexts, studies of behavioral contexts other than mating and vocalization categories other than USVs have been limited. By improving our understanding of the vocalizations emitted by mice across behavioral contexts, we will better understand the natural vocal behavior of mice and better interpret vocalizations from mouse models of disease. Hypothesizing that mouse vocal behavior would differ depending on behavioral context, we recorded vocalizations from male CBA/CaJ mice across three behavioral contexts including mating, isolation, and restraint. We found that brief restraint elevated blood corticosterone levels of mice, indicating increased stress relative to isolation. Further, after three days of brief restraint, mice displayed behavioral changes indicative of stress. These persisted for at least two days after restraint. Contextual differences in mouse vocal behavior were striking and robust across animals. Thus, while USVs were the most common vocalization type across contexts, the spectrotemporal features of USVs were context-dependent. Compared to the mating context, vocalizations during isolation and restraint displayed a broader frequency range, with a greater emphasis on frequencies below 50 kHz. These contexts also included more non-USV vocal categories and different vocal patterns. We identified a new Mid-Frequency Vocalization, a tonal vocalization with fundamental frequencies below 18 kHz, which was almost exclusively emitted by mice undergoing restraint stress. These differences combine to form vocal behavior that is grossly different among behavioral contexts and may reflect the level of anxiety in these contexts.